2017
DOI: 10.1177/1528083717740764
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of fabric reinforcement parameters on the mechanical properties of textile-based hybrid composites by full factorial experimental design method

Abstract: In this study, the effect of some fabric reinforcement parameters (fabric direction, yarn type and stacking sequence) on the mechanical properties of textile based hybrid composites are analysed by using full factorial experimental design method. The analysis of the results is achieved by using Minitab 17 software program. One factor (fabric reinforcement direction) with two levels (warp direction and weft direction) and two factors (yarn type and stacking sequence) with three levels (jute/glass, jute/carbon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In comparison, a 10.21% increase exists in UG samples, which is ascribed to the 5G-4B-5G configuration in which more number of high-tensile basalt fibers exist in the core. Similar observation was also reported by Sezgin and Berkalp 29 in E-glass/carbon fiber–reinforced with polyester resin. The tensile strength values of HG and HB samples are 356.39 and 244.22 MPa, respectively, which accounts to an increase of 31.48% in HG samples.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In comparison, a 10.21% increase exists in UG samples, which is ascribed to the 5G-4B-5G configuration in which more number of high-tensile basalt fibers exist in the core. Similar observation was also reported by Sezgin and Berkalp 29 in E-glass/carbon fiber–reinforced with polyester resin. The tensile strength values of HG and HB samples are 356.39 and 244.22 MPa, respectively, which accounts to an increase of 31.48% in HG samples.…”
Section: Resultssupporting
confidence: 90%
“…Kumar et al 28 investigated the flexural strength of hemp, basalt, and hemp/basalt epoxy and found that the damage of hybrid composite is relatively higher than that of basalt composite. Many hybrid works have been attempted using glass fiber with carbon, 29 jute, 30 flax, 31 kevlar, 32 and sisal 33 fibers, which conveys that the hybridization improves mechanical and thermal properties. Dorigato and Pegoretti 34 studied the identical structures of basalt and glass fibers and revealed that the hybridization of basalt fibers increases the impact energy, paving the way toward basalt fiber usage instead of glass fiber in engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, analysis of variance (ANOVA) which examines the fitting, significances, and preciseness of the model is performed. 34 In such cases, fewer number of experiments are performed as compared with the full factorial design. Such designs are useful when the number of potential factors is greater than two because they reduce the total number of runs required for the overall experiment.…”
Section: Methodsmentioning
confidence: 99%
“…According to Sezgin and Berkalp [12], reinforcement parameter directly affects the mechanical properties of the composites than matrix parameters. Since the research work was executed on the hand layup method, the machine-related parameters influence was minimal.…”
Section: Taguchi L9 Orthogonal Arraymentioning
confidence: 99%